Accurately Locating Metastatic Foci in Lymph Nodes With Lugol’s Iodine-Enhanced Micro-CT Imaging - Xia, Cheng-Wan; Hu, Shi-Qi; Zhou, Qun-Zhi; Gan, Rong-Lin; Pan, Jiong-Ru; Zhang, Qian; Pu, Yu-Mei; Chen, Shen; Hu, Qin-Gang; Wang, Yu-Xin (Frontiers in Oncology, 2021)
Background Accurate evaluation of lymph node (LN) status is the key factor to determine the treatment and evaluate prognosis for patients with cancer. However, traditional pathological examination resulted in a 30% false-negative rate of detection of metastases in LNs. This study aimed to utilize Lugol’s iodine (I2-IK)-enhanced micro-CT imaging to reveal the 3-dimensional structure of regional LNs and decrease the false-negative rate in pathological examination. Methods To explore the feasibility of I2-IK-enhanced micro-CT imaging in locating metastatic lesion in LNs, nonmetastatic and metastatic LNs from mice were used to mimic the imaging process. Then, the LNs from oral squamous cell carcinoma (OSCC) patients were applied to verify the value of I2-IK-enhanced micro-CT imaging in revealing LN structure and locating metastatic lesions in LNs. The glycogen content in nonmetastatic and metastatic LNs was further detected by the use of a glycogen assay kit and periodic acid–Schiff (PAS) staining to explain the imaging differences between them. Results In nude mice, 0.5% I2-IK staining for 4 h was the best parameter for normal LN. The metastatic foci in metastatic LNs were also clearly outlined in this condition. For nonmetastatic LNs from patients with OSCC, 1% I2-IK staining for 12 h was the best parameter. However, due to the increased volume of metastatic LNs, the image effect of 3% I2-IK staining for 12 h was superior to 1% I2-IK staining [tumor background ratio (TBR), 3% vs. 1%, 1.89 ± 0.10 vs. 1.27 ± 0.07, p < 0.001]. Compared with subsequent pathological sections, we found the CT intensity of metastatic foci in LNs and muscle tissues was significantly higher than in nonmetastatic regions. Meanwhile, the glycogen content of metastatic foci in LNs detected was also significantly higher than in nonmetastatic region. Conclusions I2-IK-enhanced micro-CT imaging could identify the spatial location of metastatic foci in LNs. This will be an effective method to assist in decreasing the LN false-negative rate for cancer pathology.